Gonçalves Dias, Machado de Assis e Racionais Mc’s: a invenção do centro - Valmir Luis Saldanha da Silva (IdeAs)
In this paper, based on studies of social psychology, anthropology, sociology, and literature on the Brazilian national character, we observe the role that the social and historical structure in the 19th and 20th centuries played in the situation of black and mestizo intellectuals in Brazil. We analyzed how the institutionally authorized space influenced the proposition and evaluation of works by Gonçalves Dias (1823-1864) and Machado de Assis (1839-1908) and how the Racionais Mc's group (1988-) sought to modify the hegemonic aesthetic-social structure until then through the reorganization of the discourse of black and peripheral Brazilian subjects.